Curriculum Design and Teacher Educators’ Digital Competence: Promoting Learner-Centered Teaching Approach in Higher Institutions of Learning - David Kakeeto; Anthony Muwagga Mugagga; Ronald Bisaso (Britain International for Academic Research (BIAR) Publisher, 2020)
The study was set out to establish how curriculum design influences teacher educators’ digital competence at Makerere University. It was hypothesized that, curriculum design influences teacher-educators’ digital competence. A case study design was employed taking a quantitative approach. Participants were teacher trainers from School of Education and data were collected using a self-administered questionnaire. Data were analyzed using Pearson Product moment Correlation coefficient. Results indicated that, curriculum design and development has got a significant positive influence to teacher educators’ technology knowledge and skills. It was concluded that; any curriculum that does not include technology knowledge and skills is not aimed at addressing the needs of the 21st century learners, whom we refer to as digital natives and therefore all institutions must take ICT integration as a fundamental component of today’s teaching and learning. And it was recommended that; The School of Education should develop an evaluative instrument to regularly assess the extent to teacher trainers in all departments implement technology knowledge and skills in teaching and learning process.